Differences in Collaboration Patterns across Discipline, Career Stage, and Gender - Zeng, Xiao Han T.; Duch, Jordi; Sales-Pardo, Marta; Moreira, João A. G.; Radicchi, Filippo; Ribeiro, Haroldo V.; Woodruff, Teresa K.; Amaral, Luís A. Nunes (PLOS Biology, 2016)
An empirical analysis of researchers’ publications reveals that females have fewer distinct coauthors yet have a lower chance of repeating previous coauthors than their male counterparts.